Blended learning in the context of supervised observation internship: possibilities and challenges - Fernandes , Amanda Cristiane Gonçalves (2022)
The functionality of the school space and teaching is intrinsically linked to the supervised internship, which, in turn, is based on the observation of several aspects, enabling a search for innovations in the teaching-learning process through dialogues and readings. The objective of this study is to present theoretical elements that characterize the discussion about the internship and its relations in the teaching-learning process with practice. The methodology adopted is exploratory, through a bibliographic survey, reading and critical analysis of the topics covered in the report. There was a theoretical basis with online classes and availability of bibliographic material for readings, which allowed an understanding of teaching practice in the construction of knowledge and the school space. Through the problematization discussed in the classes, a critical analysis of the obstacles that the Geography teacher deals with since his formation until the relationship in the teaching-learning process was made possible. It was possible to perceive how much practice, theory are inseparable, and how important this experience in the discipline of Geography is. Allowing teaching and learning to be integrative, with an emancipatory education, where students interact (graduates), participate and learn regardless of their difficulties.